PERANAN FAMILY ALTAR DALAM PENINGKATAN KUANTITATIF JEMAAT GEREJA BETHEL INDONESIA KASIH KARUNIA MEDAN - Sang Putra Immanuel Duha (JURNAL IMPARTA, 2022)
In simple terms, the main purpose of Family Altar is family fellowship with Christ. Increased Bible knowledge. An important condition for the success of the Family Altar is a relaxed, warm and pleasant atmosphere. The Family Altar format should be flexible, not rigid. Changes must be able to occur according to changes in schedules, ages, interests of family members. FA (Family Altar) is the smallest container unit in a local church. In it there are pastoral functions, discipleship and preparation for the birth of a leader. Today the majority of rapidly growing churches are generally supported by the dynamic Family Altar network. A healthy church is a church that shepherds its congregation into the Family Altar. The motto of the Family Altar is: Unity of Heart, Growing Together and Winning Souls.